The Effect Of Partner Capabilities, Economic Benefits And Trust To Continue Channel Partnership by MSMEs - Mohammad Syukron Aliyafi'iy; Sanaji (Journal of Business and Management Review, 2021)
The development of a business model requires SMEs to develop and strive to make their business run smoothly and develop for the better. Therefore, to catch up with big business competitors, it requires business cooperation. This study aims to determine the effect of partner capabilities and economic benefits on the decision to continue a business partnership that mediated by trust. To analyze the model, this study used 80 SMEs that partnered with Lamongan Mart. We used the partial least square (PLS) method to test the hypothesis. The results show that there is a significant effect of partner capability on trust. Economic benefits have a significant effect on trust. The decision to continue the partnership is significantly influenced by the partner's capabilities and economic benefits. Trust has a significant effect on the decision to continue the partnership. In conclusion, trust can mediate partner capabilities and economic benefits to the decision to continue the partnership.